2018
DOI: 10.1038/s41598-018-25883-x
|View full text |Cite
|
Sign up to set email alerts
|

Humanizing Miniature Hearts through 4-Flow Cannulation Perfusion Decellularization and Recellularization

Abstract: Despite improvements in pre-clinical drug testing models, predictability of clinical outcomes continues to be inadequate and costly due to poor evidence of drug metabolism. Humanized miniature organs integrating decellularized rodent organs with tissue specific cells are translational models that can provide further physiological understanding and evidence. Here, we evaluated 4-Flow cannulated rat hearts as the fundamental humanized organ model for cardiovascular drug validation. Results show clearance of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“… describes a decellularization process through the venous and arterial system. Many recellularization and reendothelialization studies have been conducted since 2008 , with direct injection (multiple injections) into the ECM and the infusion of the endothelial cells via the coronary arteries or venous inlet (e.g. multistep infusion and recirculation) being the most commonly applied methods.…”
Section: Heartmentioning
confidence: 99%
See 1 more Smart Citation
“… describes a decellularization process through the venous and arterial system. Many recellularization and reendothelialization studies have been conducted since 2008 , with direct injection (multiple injections) into the ECM and the infusion of the endothelial cells via the coronary arteries or venous inlet (e.g. multistep infusion and recirculation) being the most commonly applied methods.…”
Section: Heartmentioning
confidence: 99%
“…Xenogenic cell‐scaffold combinations are possible (e.g. mouse ECM and human cells) , as described in the study performed by Lu et al ., who showed that mouse heart scaffolds were recellularized with human multipotent cardiovascular progenitor cells derived from iPSCs or ESCs. The authors further studied cellular differentiation within the matrix, their functional interaction and the scaffold reactions to inotropic drugs .…”
Section: Heartmentioning
confidence: 99%
“…We used a protocol adapted from Gao et al (2015) , in which rat spleens were decellularized with detergent (SDS) at a concentration lower than that used for other organs ( Ott et al, 2008 ; Sullivan et al, 2012 ; Nguyen et al, 2018 ; Robertson et al, 2018 ). The lower the concentration and variety of detergents used, the greater the preservation of delicate ECM components of spleen.…”
Section: Discussionmentioning
confidence: 99%
“…The close similarity of dECM to the natural tissue niche has inspired extensive research for its utilization not only for therapeutic tissue regeneration but also for in vitro disease modeling, drug screening, cell culture optimization, and cell biology research. While native dECM scaffolds have been widely utilized for various in vitro applications, their further processing offers greater reproducibility and scalability, which are essential for developing a commercial platform. Moreover, the cutting‐edge possibilities to control spatial cell distribution, as well as the final scaffold features and composition, take 3D models to the next level, offering higher‐fidelity recapitulation of any physiological condition.…”
Section: Applications Of Processed Decm‐based Materialsmentioning
confidence: 99%